L’industrialisme à l’épreuve de la « société de l’information » - Bruno Raoul (Communication)
The crisis in Fordism has lead to a new industrial economy being structured over the last two decades. In a context marked by the deregulation and globalization of firms and markets the new economy can be discerned by notions of network economies, by tertiarialization of production and of non-material work. As with the development of new information and communication technologies, there has also been a mobilization of the social technologies of communication (management, marketing, and advertising). This article attempts to show how it is now possible to understand communication as the matrix of a new industrialism, to show the follies of prophetic theses regarding the « information society » and point out its problems on a theoretical level.